Spin current nano-oscillator (SCNO) as a potential frequency-based, ultra-sensitive magnetic biosensor: a simulation study. (30th June 2020) - Saha, Renata; Wu, Kai; Su, Diqing; Wang, Jian-Ping
Abstract: This work is a micromagnetic simulation-based study on the GHz-frequency ferromagnetic resonances (FMR) for the detection of magnetic nanoparticles (MNPs) using spin current nano-oscillator (SCNO) operating in precession mode. Capture antibody-antigen-detection antibody-MNP complex on the SCNO surface generates magnetic fields that modify the FMR peaks and generate measurable resonance peak shifts. Moreover, our results strongly indicate the position-sensitive behavior of the SCNO biosensor and demonstrate ways to eradicate this effect to facilitate improved bio-sensing. Additionally, a study has been made on how MNPs with different sizes can alter the SCNO device performance. This simulation-based study on the SCNO device shows the feasibility of a frequency-based nano-biosensor with the sensitivity of detecting a single MNP, even in presence of background noise.